Provider assessment of the temporomandibular joint in Juvenile idiopathic arthritis: a retrospective analysis from the CARRA database - Anna Costello; Marinka Twilt; Melissa A. Lerman; for the CARRA Registry Investigators (BMC, 2024)
Abstract Background Temporomandibular joint (TMJ) involvement is an often underrecognized complication of juvenile idiopathic arthritis (JIA) that can cause decreased mandibular growth, altered facial morphology, and orofacial pain. It is estimated that the TMJ is affected in 30-45% of children with JIA. Standardized physical examination and imaging evaluations are important in accurately assessing active TMJ arthritis and sequalae. Little is known about the rate at which providers evaluate TMJ involvement in their clinical practice. Methods Data were obtained from the Childhood Arthritis and Rheumatology Research Alliance (CARRA) Registry. Data fields related to assessment for TMJ arthritis were added in 2019. Patients were included in the study if they had a diagnosis of JIA and had data recorded between January 2020 and August 2021. Standard descriptive statistics were used to describe demographic and clinical features. Results A total of 17,761 visits were reviewed for a total of 7473 patients with JIA. A total of 52.7% of patients had maximal mouth opening (MMO) recorded as finger breadths or total incisal distance (TID). Only 8% had TID measured. A total of 5.0% had MRI with contrast performed. A total of 939 patients had a diagnosis of TMJ arthritis. Of these, 28.5% had an MRI documented, 83% had an MMO documented, and 40% had TID measured. Few patient-level characteristics were statistically related to having MMO assessed. MRI was more likely to be obtained in older and in female patients. MMO was recorded at a given visit > 80% of the time at 17 sites, and it was recorded < 1% of the time at 8 sites. MRIs were infrequently performed at all sites, with 27 sites having no MRIs obtained and only 7 sites having an MRI obtained at > 10% of visits. Conclusions MMO is not consistently measured in patients with JIA, and it is rarely measured quantitatively. Similarly, TMJ MRIs are rarely obtained in patients with JIA. Site of care is more associated with TMJ assessments than patient-level characteristics. These data suggest that provider education is needed to improve the assessment of the TMJ in patients with JIA to enable earlier recognition and prevent long-term complications.